Ruptura familiar por separación conyugal y depresión en un estudiante de 19 años - Gutierrez Garcia, Carla Graciela (2019)
This case study aims to establish a psychotherapeutic scheme and prove its usefulness in the treatment of a student with depression due to family breakdown due to marital separation. The case develops from the arrival of a patient along with their mother psychological consultation for depression problems; for which the pertinent psychological evaluation was carried out in the same way the scientific and theoretical revision of the variables. They were also used for the collection of information, techniques such as medical history, interview and psychometric tests, which allowed case development to reach a structural diagnosis that allowed establishing a personalized therapeutic scheme with general goals to be met and thus reducing the symptoms presented for the patient with depression